THE INFLUENCE OF SOCIAL MEDIA CONTENT AND SOCIAL MEDIA INTERACTION ON GENERATION Z'S PURCHASING DECISIONS THROUGH SOCIAL MEDIA - Hasanawi Hasanawi; Asyrafinafilah Hasanawi Hasanawi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Social media as a marketing tool is increasingly becoming the primary focus of companies in today's digital era. This phenomenon is inseparable from shifts in consumer behavior, where individuals increasingly rely on social media as a source of information and interaction. The use of social media as a marketing tool is increasingly becoming the focus of companies in the current digital era. This phenomenon is tied to changes in consumer behavior that increasingly depend on social media as a resource for information and interaction. This study aims to analyze the consumer behavior of Generation Z in using social media when making purchasing decisions. This research employs a quantitative method with descriptive and verification approaches. The data obtained were analyzed by describing the research object, and a verification analysis was performed, which was interpreted descriptively. The results of this study indicate that the respondents' assessments regarding social media content, social media interaction, and purchasing decisions fall into a high category. This means that most respondents agree with the positive statement items for each indicator across all variables. The results of the verification analysis show that the social media content and social media interaction variables have a positive and significant effect on purchasing decisions, both partially and simultaneously. The combined influence of the social media content and social media interaction variables on purchasing decisions is 48.00 percent.Keywords: Social Media Content, Social Media Interaction, Purchasing Decisions